1995
DOI: 10.1093/hmg/4.5.821
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the RET receptor tyrosine kinase in Hirschsprung disease

Abstract: Hirschsprung disease (HSCR), or congenital aganglionic megacolon, is the most common cause of congenital bowel obstruction with an incidence of 1 in 5000 live births. Recently, linkage of an incompletely penetrant, dominant form of HSCR was reported, followed by identification of mutations in the RET receptor tyrosine kinase. To determine the frequency of RET mutations in HSCR and correlate genotype with phenotype, we have screened for mutations among 80 HSCR probands representing a wide range of phenotypes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(142 citation statements)
references
References 0 publications
7
134
0
1
Order By: Relevance
“…For example, many different wildtype alleles of RETL1 and RETL2 could be present in the population and some of these alleles may compensate for and͞or suppress the RET loss of function mutations associated with HSCR. In a few families, activating RET mutations that result in MEN2A occasionally cosegregate with a HSCR disease phenotype (2,(25)(26)(27)(28). This observation is often postulated to be due to a difference in degree of penetrance in various tissues of the RET mutation or, alternatively, to a closely linked modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many different wildtype alleles of RETL1 and RETL2 could be present in the population and some of these alleles may compensate for and͞or suppress the RET loss of function mutations associated with HSCR. In a few families, activating RET mutations that result in MEN2A occasionally cosegregate with a HSCR disease phenotype (2,(25)(26)(27)(28). This observation is often postulated to be due to a difference in degree of penetrance in various tissues of the RET mutation or, alternatively, to a closely linked modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Families from the US and Spanish data set have already been published. 2,11,12 Because parental DNA was not available for all RET CDS mutation carriers patients, parental origin of RET CDS mutations was only searched for in 18 affected sib-pairs and 36 sporadic cases. A total of 15 de novo mutations were detected for sporadic cases.…”
Section: Methodsmentioning
confidence: 99%
“…However, the association of HSCR and MEN 2A appears to occur in 20 to 30% of families with mutations C618R or C620R (Mulligan et al, 1994b), an observation that suggests that other genetic factors might in¯uence the expression of the enteric phenotype in these families. Missense mutations at codon 609 have also been described in two HSCR families with no evidence of endocrine neoplasia (Angrist et al, 1995;Mulligan et al, 1994b) and it has been recently showed that one of these two mutations which changes the cysteine for the bulky non polar amino acid tryptophan, leads to the almost complete disappearance of the 170 kDa RET product Pelet et al, 1998). Therefore, it is conceivable that in certain circumstances, not only the position but also the nature of the mutation might contribute to the dysfunction of RET and act synergistically in determining the disease phenotype.…”
Section: Retmentioning
confidence: 99%